2017
DOI: 10.1097/ajp.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression and Risk of Low Back Pain

Abstract: The magnitude of the association between depression and LBP seems to be small and may be confounded by genetic and early shared environment influences, although firm conclusions could not be made due to small sample size in the case-control analysis. In addition, the observed association is dependent on the method of assessment used for both conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…This should be considered when interpreting the results of this study, given that genetic influence is higher for more disabling and chronic types of low back pain (Ferreira et al, 2013). Similarly, we assessed symptoms of depression and anxiety, rather than depression diagnosed by a health professional or a specific questionnaire, and previous studies have shown that the definition and measurement method used for assessing depression impact on its relationship with low back pain (Pinheiro et al, 2015b, Pinheiro et al, 2016.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This should be considered when interpreting the results of this study, given that genetic influence is higher for more disabling and chronic types of low back pain (Ferreira et al, 2013). Similarly, we assessed symptoms of depression and anxiety, rather than depression diagnosed by a health professional or a specific questionnaire, and previous studies have shown that the definition and measurement method used for assessing depression impact on its relationship with low back pain (Pinheiro et al, 2015b, Pinheiro et al, 2016.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In light of the moderate to large effects of genetic factors on low back pain (Ferreira et al, 2013) and depression (Sullivan et al, 2000), our research group has recently investigated the relationship between low back pain and symptoms of depression and anxiety while accounting for genetic and environmental factors by employing a co-twin case-control design (Pinheiro et al, 2015a, Pinheiro et al, 2016. The findings from…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…52 To our knowledge, this is the first longitudinal co-twin control study to show a significant association between a psychological risk factor and incident back pain in sizes. 22,23 Another potential limitation of the longitudinal co-twin control design using binary outcomes is the typical practice of restricting the baseline sample to twin pairs where both co-twins do not have the outcome at baseline, as was done in our study.…”
Section: Two Prior Longitudinal Studies In Clinical Samples Of Patienmentioning
confidence: 99%
“…[ 1 2 ] Pinheiro et al . in their follow-up study, “Symptoms of Depression and Risk of LBP: A Prospective Co-Twin Study,[ 3 ]” attempted to investigate whether symptoms of depression increase the risk of chronic LBP with the use of a prospective study design, but with the important adjustment for important confounders including genetic factors, thus the utilization and inclusion of twins.…”
mentioning
confidence: 99%
“…Although their results did not suggest a possible causal link between depression and LBP (given that no association was found, when genetic and early environmental factors are controlled for), their study did in fact find a significant association between trait depression and future care seeking and activity-limiting LBP. [ 3 ] Now, for providers in training and those already practicing, this is an important point to take notice of.…”
mentioning
confidence: 99%